THE ROLE OF FOREST BATHING IN THE TREATMENT OF DEPRESSION- A NARRATIVE REVIEW - Klaudia Zackiewicz; Michał Ziemba; Agata Wińska; Oliwia Sędziak; Hanna Pietruszewska; Agata Ogórek; Irmina Czerepak; Izabela Majchrzak; Paweł Liszka; Karolina Żylińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Forest bathing (shinrin- yoku) is a Japanese practice, involving immersion in forested areas with engaging all five senses. Its potential preventive benefits have increasingly attracted interest within the international scientific community, since forest bathing appears to be a safe and low- cost complementary approach, while offering therapeutic value. This narrative review summarizes current evidence on the physiological and psychological benefits of forest therapy, with particular focus on its importance in the treatment of depression- a prevalent mental health disorder, that affects approximately 332 million people worldwide. Studies showed that forest bathing alleviates depressive symptoms, reduces stress, increases feelings of relaxation, happiness and overall mental well being, through several biological pathways, including serotonin modulation, oxytocin increase, cortisol reduction and increased parasympathetic activity. However, further high quality research is needed to clarify its clinical value and long term effects in the treatment of depression. Methodology: A narrative review of literature available in the PubMed database was undertaken, incorporating recent randomized controlled trials, cohort studies, and meta-analyses published in peer- reviewed journals. Articles were searched in English using key terms such as: forest bathing, shinrin- yoku, nature therapy, depression.